Characteristics of Peripheral Arterial Disease Patients in Vascular and Endovascular Surgery Department Dr. Mohammad Hoesin General Hospital between January 2018 - December 2019 - Gayuh Prasetya; Fahmi Jaka Yusuf; Kemas Dahlan (Sriwijaya Journal of Surgery, 2021)
Background: Peripheral artery disease (PAD) is a chronic occlusive arterial disease of the extremities caused by atherosclerosis leading to stenosis or occlusion characterized by decreased blood flow to the limb, due to obstruction or narrowing of the blood vessels. PAD often underdiagnosed and poorly understood. ​​Median annual expenditure per individual for patients with PAD was $ 11.553 to $ 42.613 in the United States. The lack of data on PAD in South Sumatra was the based for investigators to conducting this study. Methods: This research is a retrospective descriptive study. The purpose of this study was to describe the characteristics of PAD patient based on the Rutherford classification. There are 33 cases in this study. Results: The dominant patient was male, the youngest age was 28 years old and the oldest age was 71 years, with a mean age of 55.8 years. Diabetes mellitus, stage 1 hypertension, LDL more than 100 mg/dL, ABI results that showed PAD, and stage 2 Rutherford were the dominant cases in the sample of this study. Conclusion: Early prevention and treatment from vascular and endovascular surgery can be considered as the most important for the management of peripheral arterial disease patient.